2003
DOI: 10.1177/230949900301100202
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Indicators for Outcome following Rotator Cuff Tear Repair

Abstract: Ageing was found to be the major factor in progressive degeneration of the rotator cuff, and should be considered the single most important contributing factor in the pathogenesis of rotator cuff tears. In addition, degenerative tendonopathy appeared the primary pathology in rotator cuff tear, preceding hypertrophic spur formation. Rotator cuff tears are therefore unlikely to be initiated by impingement; rather, they develop as an intrinsic degenerative tendonopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 19 publications
(21 reference statements)
2
37
1
Order By: Relevance
“…Charousset et al [7] reported female gender was a negative predictive factor for improvement of clinical results. However, Feng et al [12] reported gender was not correlated with postoperative outcome. There is no consensus regarding this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Charousset et al [7] reported female gender was a negative predictive factor for improvement of clinical results. However, Feng et al [12] reported gender was not correlated with postoperative outcome. There is no consensus regarding this issue.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported preoperative factors influencing functional outcomes after rotator cuff repair (Table 1). Feng et al [12] reported aging was the main factor in progressive degeneration of the rotator cuff and aging should be considered the most important factor contributing to the pathogenesis of rotator cuff tears. Age-dependent decline of healing potential in degenerated rotator cuffs and age-dependent progression of shoulder dysfunction caused by rotator cuff tears have been observed [4,26].…”
Section: Discussionmentioning
confidence: 99%
“…Factors most commonly considered to have an effect on postoperative outcome are age, gender, smoking status, and tear size [2,8,10,12,16,17,18,22,23,29,33,34,36,39,41,44]; contradictory results have been reported, with some studies suggesting these factors do have an impact on outcome [8,10,12,22,29,36,41,44] and others suggesting they do not [16-18, 23, 33, 34, 39]. However, to our knowledge, no study has explored whether these factors affect patients with compensation claims differently from those without compensation claims (eg, do large tears have a worse outcome in WCB recipients than nonrecipients; does smoking have a different impact on outcome in WCB recipients than nonrecipients?).…”
Section: Introductionmentioning
confidence: 99%
“…9 Several retrospective studies have tried to evaluate the etiology of rotator cuff injuries and have found that 40% to 72% of patients report trauma in the history before their shoulder problems occurred. 4,8,9,11,15,20 Nevertheless, the majority of studies published have been concerned with the diagnosis and treatment of chronic rotator cuff lesions,* and only sparse attention has been given to evaluating the differences between acute, traumatic and chronic rotator cuff tears (RCTs) and thereby improving the early diagnosis of traumatic tears.For chronic cases of full-thickness RCTs, magnetic resonance imaging has previously been considered the most precise diagnostic tool, but during the last decade, further improvements in equipment and technique have now shown similar results with sonography, 6 with sensitivities and specificities ranging from 80% to 100% for both modalities. With the impression that some acute RCTs may be missed during initial examination in emergency departments and with limited knowledge about the incidence of these tears, this study was designed as a prospective investigation to evaluate clinical tests and imaging metha From the…”
mentioning
confidence: 99%
“…9 Several retrospective studies have tried to evaluate the etiology of rotator cuff injuries and have found that 40% to 72% of patients report trauma in the history before their shoulder problems occurred. 4,8,9,11,15,20 Nevertheless, the majority of studies published have been concerned with the diagnosis and treatment of chronic rotator cuff lesions,* and only sparse attention has been given to evaluating the differences between acute, traumatic and chronic rotator cuff tears (RCTs) and thereby improving the early diagnosis of traumatic tears.…”
mentioning
confidence: 99%